Republic of Croatia : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; Staff Statement; and Statement by the Executive Director for the Republic of Croatia. (IMF Staff Country Reports; Country Report ;, 2010)
Croatia's economy is also saddled with more pervasive rigidities and higher government involvement than many of its transition peers. The Croatian National Bank (CNB) pursued proactive policies, which helped ensure financial sector stability. A stable nominal exchange rate provided an anchor for inflation expectations and financial stability, but also contributed to the accumulation of vulnerabilities. Croatia's fiscal policy did not take sufficient advantage of the boom years to create adequate space for demand management. Economic recovery is expected to be gradual, with positive growth resuming in the second half of 2010.